Ni–PC@SBA-15 derived from nano-sized Ni-MOF-74 confined in SBA-15 as a highly active catalyst for gas phase catalytic hydrodechlorination of 1, 2-dichloroethane. Issue 51 (21st May 2020) - Ning, Xin; Deng, Dongzhi; Fu, Heyun; Qu, Xiaolei; Xu, Zhaoyi; Zheng, Shourong
Abstract : A novel Ni-porous carbon composite confined in SBA-15 was fabricated for highly effective and selective gas phase catalytic hydrodechlorination of 1, 2-dichloroethane. Abstract : A novel catalyst consisting of metallic Ni and porous carbon (PC) confined in SBA-15 was fabricated by the confined pyrolysis of nano-sized Ni-MOF-74 that was in situ grown in the mesopores of SBA-15. Due to the intimate contact between Ni and PC in a fine Ni–PC composite resulting from the confinement effect of mesoporous SBA-15, the catalyst displayed prominent catalytic activity and selectivity in the gas phase catalytic hydrodechlorination of 1, 2-dichloroethane.